Coastal and Indigenous community access to marine resources and the ocean: A policy imperative for Canada. (January 2018) - Bennett, Nathan J.; Kaplan-Hallam, Maery; Augustine, Gerry; Ban, Natalie; Belhabib, Dyhia; Brueckner-Irwin, Irene; Charles, Anthony; Couture, John; Eger, Sondra; Fanning, Lucia; Foley, Paul; Goodfellow, Anne Marie; et al.
Abstract: Access, defined as the ability to use and benefit from available marine resources or areas of the ocean or coast, is important for the well-being and sustainability of coastal communities. In Canada, access to marine resources and ocean spaces is a significant issue for many coastal and Indigenous communities due to intensifying activity and competition in the marine environment. The general trend of loss of access has implications for these communities, and for Canadian society. In this review and policy perspective, we argue that access for coastal and Indigenous communities should be a priority consideration in all policies and decision-making processes related to fisheries and the ocean in Canada. This paper reviews how access affects the well-being of coastal communities, factors that support or undermine access, and research priorities to inform policy. Recommended actions include: ensuring access is transparently considered in all ocean-related decisions; supporting research to fill knowledge gaps on access to enable effective responses; making data accessible and including communities in decision-making that grants or restricts access to adjacent marine resources and spaces; ensuring updated laws, policies and planning processes explicitly incorporate access considerations; and, identifying and prioritizing actions to maintain and increase access. Taking action now could reverse the current trend and ensure that coastal and Indigenous communities thrive in the future. This is not just a Canadian issue. Globally, the ability of coastal and Indigenous communities to access and benefit from the marine environment should be at the forefront in all deliberations related to the oceans. Highlights: Access to marine resources and the ocean is important for the well-being of coastal communities. In Canada, access is a growing issue for many coastal and Indigenous communities. We examine factors that support or undermine access, research needs, and recommended actions. Community access should be given priority in decisions related to fisheries and the ocean. Taking action now will ensure that coastal and Indigenous communities thrive in the future.